PRODUCTION OF OXYGEN FROM AQUEOUS WATER USING THE PRINCIPLE OF INDUCED CURRENT: Received: 11th May 2021; Revised: 23rd November 2021, 7th December 2021, 27th December 2021; Accepted: 30th December 2021 - Onn, Kin Low; Tong, Khoo Kee; Yao, Koon Ying; Xin, Chua Jia (MATTER: International Journal of Science and Technology, 2022)
This is a fundamental research work aimed to investigate an alternative route other than the photosynthesis process where oxygen can be generated naturally and then accumulated in the atmosphere. The authors proposed a magnetosynthesis process for this investigation. This is a very important topic so that the real reason our atmosphere could accumulate sufficient oxygen for life can be reviewed. In addition, oxygen produced in this way may possess different properties other than that from photosynthesis. The lifestyle of living could be greatly improved in the case scientist could understand this method adequately. In this work, the authors utilised the advanced water filtration method so that majority of the original dissolved oxygen can be expelled away from tap water to the atmosphere. The water with low oxygen content was able to absorb as generated oxygen as dissolved oxygen in the filtered water. This can bring an indication for measurement once oxygen is generated by the magnetosynthsis process. The authors found that oxygen can be produced as dissolved oxygen when a stream of water flows through a magnetic field. Electrons shall be produced when moving aqueous water molecules flow through the magnetic field according to the principle of induced current. Oxygen shall be forced to free off from aqueous water molecules when they received electrons. A mechanism by which oxygen can be free off from water molecules is proposed in this work. When oxygen is produced, the oxygen shall dissolve in the water system until its solubility limit is achieved. Excessive oxygen exceeding the solubility limit is thought to escape to the atmosphere.